Advances in Communication Systems and Electrical Engineering - Huang, Xu.; Chen, Yuh-Shyan.; Ao, Sio-Iong.; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Advances in Communication Systems and Electrical Engineering compiles revised and extended articles written by prominent researchers participating in the IAENG International Conference on Communication Systems and Applications, IAENG International Conference on Internet Computing and Web Services, and IAENG International Conference on Electrical Engineering of the International MultiConference of Engineers and Computer Scientists (IMECS) 2007. This volume presents the latest technologies and applications in wireless networks, telecommunication, and signal processing. Topics covered in this book include: Communications theory Communications protocols Network management Power engineering Advances in Communication Systems and Electrical Engineering offers the latest information on the advances in communication systems and electrical engineering and serves as an excellent reference work for researchers and graduate students working in this area.
Cooperative Transmission to Increase Gain by Employing Pre-Coding Scheme -- High Capacity and Reliable Technique for Wireless Personal Area Networks -- Including Adaptive Behavior in a Wireless Network System -- Classification Technique Using Neural Networks and Clustering Architecture for Wireless Sensor Networks -- PALMS: A Reliable and Incentive-Based P2P Live Media Streaming System -- A Novel Dynamical Compressing of XML Data for Transmission on Networks -- An Authenticated Key Management Scheme for Hierarchical Wireless Sensor Networks -- A New Approach in Scheduling for Differentiated Service Networks -- Novel Cooperative Transmission Technique of OFDMA Systems with Multiple Antennas for Broadband Wireless Access -- HJM Tree for Security Analyses of Passive RFID Systems -- Reliability, Capacity, and Energy Efficiency: A Comprehensively Optimized MAC Protocol for Industrial Wireless Sensor Networks -- A Self-administrative Sub-role Based Delegation Model for BMI Systems -- An Intelligent Maintenance System with Open Source Software -- Further Research on Web Service-Oriented Asynchronous Invoking -- An Analysis of Man-machine Interaction in Instant Messenger -- Filtering Spam Email with Flexible Preprocessors -- Web OpinionPoll: Extensive Collection and Impression-based Visuatlization of People$1 (Bs Opinions -- The Categorical Distinction Annexations to Maximal Associations Discovered from Web Database by Rough Set Theory and Increase the Quality -- Business Logic Description by End-User for Web Service Integration Based on Abstract Forms -- OPTIMISE: An Internet-Based Platform for Metamodel-Assisted Simulation Optimization -- Natural Language Processing Methods for Extracting Information From Mathematical Texts -- Investigation of the Effectiveness of Tag-Based Contextual Collaborative Filtering in Website Recommendation -- Context-Aware Ranking Method for Information Recommendation -- Multiplierless Synthesis of Multiple Constant Multiplications Using Common Subexpression SharingWith Genetic Algorithm -- Design of Intelligent Controllers Using Online-Trained Fuzzy Neural Networks of the UPFC -- Use of Soft Computing Components to Improve Transient/Steady-state of Control Systems -- Design and Implementation of UHF Antennas for UAV Radio Link -- Efficient 2D Linear-Phase IIR Filter Design and Application in Image Processing -- Image Enlargement Based on Low to High Frequency Components Mapping Derived from Self-decomposed Images -- Contour Descriptor Based on Affine Invariance Normalization -- Adaptive Difference of Gaussian for Speed Sign Detection in Night-times Conditions -- Binarization of Engineering Drawings Using Adaptive Thresholding Techniques -- A Robust Watermarking Scheme for Digital Images Using Self Reference -- A Robust OCR for Degraded Documents -- Distortion Tolerant Color Pattern Recognition by Using Mach-Zehnder Joint Transform Correlator with Image Encoding Technique -- Approach to the Chinese Seal Registration -- Automatic Localization and Segmentation of Blood Vessels, Optic Disc and Macula in Digital Funuds Images -- Denoising in the Wavelet Domain Using Double Filtering -- A New Linear Appearance Based Method in Face Recognition -- A Meta-search Engine with Hits Redundancies Filtering.s
Keywords: Engineering; Energy; Computer organization; Computer communication systems; Electrical engineering; Engineering; Communications Engineering, Networks; Computer Communication Networks; Signal, Image and Speech Processing; Electrical Engineering; Computer Systems Organization and Communication Networks; Energy, general; Electronic books